How to help your depressed friend? The effects of interactive health narratives on cognitive and transformative learning - Scholl, Jasper; Pandrea, Markus; van Enschot, Renske (Frontiers in Communication, 2022)
Using narratives is an important communication strategy in mental health campaigns to empower readers to adequately help people suffering from depression. These narratives could be enhanced by giving readers agency to make choices on behalf of the main character that noticeably affect the narrative. Yet, few studies have explored the effects of these choices. This study investigated the effects of agency in an interactive digital narrative (IDN) about depression on cognitive and transformative learning. In two experimental, between-subjects design studies, the learning outcomes of a traditional (without agency) and interactive version (with agency) of a narrative about depression were compared. The mediating roles of identification, transportation and intrinsic motivation were also considered. In Experiment 1 (N = 216), no effects of agency on cognitive learning, intrinsic motivation, identification or transportation were found. After better embedding learning content and increasing the choices’ meaningfulness in the narrative of Experiment 2 (N = 155), agency positively affected transformative learning but not cognitive learning. The effect on transformative learning was mediated by identification with the character. These results suggest that agency in educational narratives about depression increases identification with caretakers and reflection on how to approach people with depression sensibly. Implications of these results are discussed.